A Study Of Burkholderia Pseudomallei K96243 Hypothetical Bpsl3393 Gene Product As A Putative Coa-Binding Protein - Ooi, Gim Luan (2014)
Burkholderia pseudomallei is the causative agent of melioidosis. From the whole genomic comparison by using B. pseudomallei K96243 as reference genome, a total 48 genes were found specifically and common in B. pseudomallei strains. Amongst, the hypothetical gene, BPSL3393, was deduced to contain the CoA-binding motif based on its sequence analysis. However, this gene is still remaining as a putative gene where it is still functionally uncharacterized. The objective of this study is to elucidate the biological function of gene BPSL3393 in B. pseudomallei K96243. An unmarked deletion mutant of gene BPSL3393 was constructed by using pDM4 suicidal vector. This vector employed catR, chloramphenicol resistant gene as the selection marker and sacB, levansucrase gene as the counter-selection marker. The biochemical profiles of ΔBPSL3393 mutant and wild type strains were determined by using th Biolog GN2 MicroPlateTM system. The ΔBPSL3393 mutant showed significant reduction in 2-aminoethanol utilization as compared to wild type. Apart from this, the ΔBPSL3393 mutant also has shown some physiological difference as compared to wild type. The ΔBPSL3393 mutant aggregated at the exponential phase in M9 minimal media whereas the wild type did not. Thus, further study is needed to characterize this ΔBPSL3393 mutant and to uncover its biological role.